Editorial for the Special Issue on Novel Approaches for Structural Health Monitoring II - Cecilia Surace (Applied Sciences, 2023)
The emphasis of this Special Issue is on showcasing the most recent advancements in the field of Structural Health Monitoring (SHM), accounting for all its applications in mechanical systems and civil structures or infrastructures [...]